2019
DOI: 10.1021/jacs.9b01676
|View full text |Cite
|
Sign up to set email alerts
|

Control by Metals of Staphylopine Dehydrogenase Activity during Metallophore Biosynthesis

Abstract: Enzymatic regulations are central processes for the adaptation to changing environments. In the particular case of metallophore-dependent metal uptake, there is a need to quickly adjust the production of these metallophores to the metal level outside the cell, to avoid metal shortage or overload, as well as waste of metallophores. In Staphylococcus aureus, CntM catalyzes the last biosynthetic step in the production of staphylopine, a broad-spectrum metallophore, through the reductive condensation of a pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…His(Trt)‐O t Bu ( 7 ), despite commercially available, was prepared in a three step procedure (overall yields 40–50 %) starting from Cbz‐His‐OH ( 6 , Scheme S1). Following a similar reduction/selective oxidation strategy to the one that we recently reported, we synthesized protected aspartic acid semi aldehyde (Asa), Cbz‐Asa‐O t Bu ( 9 ), starting from Cbz‐Asp‐O t Bu · dicyclohexylamine (DCHA) ( 8 , Scheme S2). Reductive amination between building blocks 7 and 9 proceeded in good yields (80 %, Scheme ) without the formation of any potential by‐product, such as tertiary amine deriving from a second reductive amination, or γ‐lactam deriving from the intramolecular attack of the secondary amine to the ester group of 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…His(Trt)‐O t Bu ( 7 ), despite commercially available, was prepared in a three step procedure (overall yields 40–50 %) starting from Cbz‐His‐OH ( 6 , Scheme S1). Following a similar reduction/selective oxidation strategy to the one that we recently reported, we synthesized protected aspartic acid semi aldehyde (Asa), Cbz‐Asa‐O t Bu ( 9 ), starting from Cbz‐Asp‐O t Bu · dicyclohexylamine (DCHA) ( 8 , Scheme S2). Reductive amination between building blocks 7 and 9 proceeded in good yields (80 %, Scheme ) without the formation of any potential by‐product, such as tertiary amine deriving from a second reductive amination, or γ‐lactam deriving from the intramolecular attack of the secondary amine to the ester group of 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Given the impact of the Cnt systems in P. aeruginosa and S. aureus infections, knowledge on metallophores production and control of metal level are highly relevant. After our recent characterization of Sa CntM (the ODH of S. aureus ), and in particular its peculiar activity modification in presence of different divalent metals, we focused on the P. aeruginosa case. The full understanding of this metal acquisition system might disclose the route to novel antimicrobial therapies that could improve the life expectation of CF or other immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of CntM have been solved in a binary/tertiary complex with NADPH or NADPH and xNA, revealing the residues that are involved in the complex formation and building the active site [8,32]. First focusing on the NADPH binding site of SaCntM (Figure 2A) we observed that the phosphate group of NADPH is sandwiched by the side chains of two positively charged residues (R33 and K39) that are rather conserved in the CntM family.…”
Section: Resultsmentioning
confidence: 99%
“…Activities from S. aureus (SaCntM) and from P. aeruginosa (PaCntM) were therefore compared for their ability to use chemically synthesized xNA and yNA as substrate (Figure 4). The chemical synthesis of xNA was recently reported [32] and we were able to synthesize yNA by following the same approaches (see the experimental procedures and the supplementary materials). Reactions were then performed in vitro using purified proteins and a concentration range of xNA and yNA with a fixed concentration of other substrates: 0.2 mM of NADPH and 1 mM of pyruvate (when evaluating SaCntM) or α-ketoglutarate (when evaluating PaCntM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation